Introduction to Byzantium, 602-1453 - Harris, Jonathan (Taylor & Francis Group, 2020)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures -- List of boxes -- List of maps -- Preface -- Introduction -- 0.1 What's in a name? -- 0.2 The study of Byzantium -- 0.3 Byzantium in 602 CE -- 0.4 The tragic end of Emperor Maurice -- Points to remember -- Suggestions for further reading -- PART I: Crisis and survival 602-820 -- 1. Major literary sources for the period 602-820 -- 1.1 Byzantine literature and education -- 1.2 Patriarch Nikephoros -- 1.3 Theophanes Confessor -- 1.4 Other types of source: hagiography and military manuals -- 1.5 Sources from outside Byzantium -- Points to remember -- Some primary sources in English translation -- Suggestions for further reading -- 2. Herakleios and the wars of survival (602-642) -- 2.1 The spiralling crisis (602-622) -- 2.2 Defeat into victory (622-629) -- 2.3 Why the war was won -- 2.4 Victory into defeat (629-642) -- 2.5 What went wrong? -- 2.6 The Balkans and the western provinces -- Points to remember -- Suggestions for further reading -- 3. The dark age (642-718) -- 3.1 The new enemy: the Umayyad caliphate -- 3.2 Constantinople under siege -- 3.3 The battle for Asia Minor -- 3.4 The reorganisation of Asia Minor -- 3.5 The Balkans and the western provinces -- Points to remember -- Suggestions for further reading -- 4. The beginnings of the revival (718-820) -- 4.1 The North Syrian dynasty -- 4.2 Iconoclasm -- 4.3 The reign of Irene (780-802) -- 4.4 The limits of revival: Bulgaria -- 4.5 The limits of revival: Italy -- Points to remember -- Suggestions for further reading -- PART II: Reconquest and hegemony 820-1045 -- 5. Major literary sources for the period 820-1045 -- 5.1 The 'Macedonian Renaissance' -- 5.2 Historians at the court of Constantine VII (945-959) -- 5.3 Leo the Deacon -- 5.4 Michael Psellos.